2013
DOI: 10.1111/flan.12013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Affective Profiles of Postsecondary Students in Lower‐Level Foreign Language Classes

Abstract: Recent surveys and research on second language (L2)/foreign language acquisition help explain the challenges that postsecondary students in lower‐level foreign language (FL) courses may experience. The present study extends this line of research by examining changes in students' affective profiles in a two‐year Japanese program (n = 382) at an American university. The results indicated that students who reached the end of the program perceived more social, economical, integrative, and other value in learning J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Busse and Walter attributed this decline to context‐specific pedagogical practices in higher education, since L2 instructors mainly taught literature in English as opposed to in the target language. While not necessarily focused on first‐year students, but first‐ and second‐year students in a four‐semester L2 Japanese program, Kondo‐Brown (2013) likewise found changes in affective states among learners over time. Specifically, over the four‐semester L2 Japanese program, learners' levels of motivation increased as they came to the end of the program; however, paradoxically, their level of effort dropped off significantly.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Busse and Walter attributed this decline to context‐specific pedagogical practices in higher education, since L2 instructors mainly taught literature in English as opposed to in the target language. While not necessarily focused on first‐year students, but first‐ and second‐year students in a four‐semester L2 Japanese program, Kondo‐Brown (2013) likewise found changes in affective states among learners over time. Specifically, over the four‐semester L2 Japanese program, learners' levels of motivation increased as they came to the end of the program; however, paradoxically, their level of effort dropped off significantly.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Specifically, over the four‐semester L2 Japanese program, learners' levels of motivation increased as they came to the end of the program; however, paradoxically, their level of effort dropped off significantly. Kondo‐Brown (2013) strongly recommended that L2 instructors pay close attention to lower‐level L2 students in higher education contexts and explicitly teach them how to “develop effective motivational strategies, internalize positive attitudes, and develop good study habits” (p. 130).…”
Section: Review Of Literaturementioning
confidence: 99%
“…And even as language advocates, especially when talking to each other, have emphasized integrative motivation and humanistic transformation, some research has shown that instrumental motivation can produce intensive engagement with the language (Gardner & MacIntyre, 1991) or that instrumental and integrative motivations need to work together (Yu, 2014). Kim (2009), Kondo-Brown (2013), and Busse and Walter (2013) further explained that motivational orientation is not static but changes over the course of language study.…”
Section: Motivation Researchmentioning
confidence: 99%
“…In the age of globalization where diversity and inclusion are valued, there is need for the investigation of motivations driving the learning of languages other than English used in different regions across the world. Responding to this call, a growing number of L2 Japanese studies address the dynamic nature of perceptual development in relation to individual, educational, sociocultural, and regional variables in motivation (Oda, 2010; Onishi, 2010; Yang, 2011; Northwood & Thomson, 2012; Kondo-Brown, 2013; Rose & Harbon, 2013; Tanaka, 2013; Mori & Takeuchi, 2016), self-systems (Kurata, 2015; Sakeda & Kurata, 2016), perceptions (Sakurai, 2012; Yoshida, 2013a, 2013b), attitudes (Jo, 2010; Zhang, 2013), anxiety (Chiba & Morikawa, 2011), and perceived learning strategies (Gamage, 2011; Grainger, 2012, 2013).…”
Section: L2 Japanese Learner Motivationmentioning
confidence: 99%
“…At the same time, the continuation of formal classroom learning does not necessarily guarantee the students’ active engagement in learning. Kondo-Brown (2013), for instance, observed that students in upper-level courses at an American university invested less effort in their coursework, despite their higher appreciation of socio-economic and integrative values in learning Japanese, than those at the beginning of the program. Similarly, Xu (2018) found that some Japanese major students in China became demotivated in the course of their study.…”
Section: L2 Japanese Learner Motivationmentioning
confidence: 99%